Gene3D: Extensive prediction of globular domains in proteins. Issue Volume 46:Issue D1(2018) (3rd November 2017) - Lewis, Tony E; Sillitoe, Ian; Dawson, Natalie; Lam, Su Datt; Clarke, Tristan; Lee, David; Orengo, Christine; Lees, Jonathan
Abstract: Gene3D (http://gene3d.biochem.ucl.ac.uk ) is a database of globular domain annotations for millions of available protein sequences. Gene3D has previously featured in the Database issue of NAR and here we report a significant update to the Gene3D database. The current release, Gene3D v16, has significantly expanded its domain coverage over the previous version and now contains over 95 million domain assignments. We also report a new method for dealing with complex domain architectures that exist in Gene3D, arising from discontinuous domains. Amongst other updates, we have added visualization tools for exploring domain annotations in the context of other sequence features and in gene families. We also provide web-pages to visualize other domain families that co-occur with a given query domain family.